2011
DOI: 10.1021/ci200216z
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Carborane Docking to Proteins and Potential Drug Targets

Abstract: The presence of boron atoms has made carboranes, C(2)B(10)H(12), attractive candidates for boron neutron capture therapy. Because of their chemistry and possible conjugation with proteins, they can also be used to enhance interactions between pharmaceuticals and their targets and to increase the in vivo stability and bioavailability of compounds that are normally metabolized rapidly. Carboranes are isosteric to a rotating phenyl group, which they can substitute successfully in biologically active systems. A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 108 publications
0
30
0
Order By: Relevance
“…The shape complementarity algorithm of PatchDock39 was used to generate docking models of lysozyme and a (10,10) CNT, probably the most representative and studied carbon nanotube. The docking poses were rescored with FireDock,40 in a protocol recently validated for the study of interaction between proteins and fullerenes41 and carborane 42. MD simulations were performed at constant pressure (1 atm) and temperature (300 K) with the AMBER 11 MD package43 by using a 2.0 fs time step (the SHAKE algorithm44 was used to constrain the stretching of bonds involving hydrogen atoms).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape complementarity algorithm of PatchDock39 was used to generate docking models of lysozyme and a (10,10) CNT, probably the most representative and studied carbon nanotube. The docking poses were rescored with FireDock,40 in a protocol recently validated for the study of interaction between proteins and fullerenes41 and carborane 42. MD simulations were performed at constant pressure (1 atm) and temperature (300 K) with the AMBER 11 MD package43 by using a 2.0 fs time step (the SHAKE algorithm44 was used to constrain the stretching of bonds involving hydrogen atoms).…”
Section: Resultsmentioning
confidence: 99%
“…The docking poses were rescored with FireDock, [40] in a protocol recently validated for the study of interaction between proteins and fullerenes [41] and carborane. [42] MD simulations were performed at constant pressure (1 atm) and temperature (300 K) with the AMBER 11 MD package [43] by using a 2.0 fs time step (the SHAKE algorithm [44] was used to constrain the stretching of bonds involving hydrogen atoms). Electrostatic interactions were calculated with the particle mesh Ewald method, [45] and threedimensional periodic boundary conditions were applied.…”
Section: Resultsmentioning
confidence: 99%
“…In Silico Generation of the Mutants . Experimental data from NMR and a docking protocol,,,,, recently validated for the study of interaction between proteins and nanoobjects were used to generate the initial coordinates of the adduct…”
Section: Computational Detailsmentioning
confidence: 99%
“…between protein and C 60 as previously described ,,,,,. The lateral chain of the residue to be mutated is deleted in the pdb file and the Trp residue is added using the tleap module in antechamber .…”
Section: Computational Detailsmentioning
confidence: 99%
“…The reason boron compounds are selected to be substituted at the ZBG and CAP is because the clinical trials have shown that consumption of boron may prevent cervical cancer caused by HPV [37, 39]. By consuming the boron content of 84.1 mg per day, it could prevent cervical cancer [40].…”
Section: Introductionmentioning
confidence: 99%